1988
DOI: 10.1136/adc.63.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal dysfunction after treatment of intracranial tumours.

Abstract: SUMMARY Ninety three children (51 boys, 42 girls) who had been treated for brain tumours not affecting the hypothalamopituitary axis, were studied for evidence of gonadal dysfunction. All had received cranial irradiation, 59 spinal irradiation, and 28 adjuvant chemotherapy. Mean age at treatment was 6-3 years (range 1.5-15). Mean follow up after completion of radiotherapy was 8-5 years (range 1-27). Primary ovarian damage occurred in seven out of 11 (64%) girls treated with craniospinal irradiation alone and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 17 publications
0
34
0
2
Order By: Relevance
“…The prevalence of POI was reported at 11.8% among female CCS exposed to these highrisk therapies (89). Survivors of CNS tumors may experience POI because of treatment with alkylating agents and ovarian exposure to radiation after craniospinal radiotherapy (119,145). Up to 25.8% of females surviving medulloblastoma experienced POI; this is a likely underestimate given the young age (median age 16.6 years) of this cohort (87, 146).…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…The prevalence of POI was reported at 11.8% among female CCS exposed to these highrisk therapies (89). Survivors of CNS tumors may experience POI because of treatment with alkylating agents and ovarian exposure to radiation after craniospinal radiotherapy (119,145). Up to 25.8% of females surviving medulloblastoma experienced POI; this is a likely underestimate given the young age (median age 16.6 years) of this cohort (87, 146).…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…Even low doses of ionizing radiation to the brain can cause intellectual impairment as well as perturbed growth and puberty. [2][3][4][5][6] RT can cause vascular abnormalities, demyelination and ultimately necrosis. 7 These problems are more pronounced for children who receive RT and the intensity of symptoms seems to be correlated with the age of the child at the time of treatment, such that the younger the child at the time of RT the more severe the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Cranial irradiation may damage the hypothalamo-pituitary axis leading to growth hormone (GH) deficiency and other endocrine dysfunction. A small number of studies have shown that spinal irradiation has an adverse effect both on spinal growth (Probert et al, 1973;Shalet et al, 1987) and on ovarian and thyroid function (Brown et al, 1983;Shalet et al, 1977a;Oberfield et al, 1986) and that some cytotoxic agents are gonadotoxic (Ahmed et al, 1983;Livesey & Brook, 1988). There has been no large unselected study of the prevalence of these disorders and their implications.…”
mentioning
confidence: 99%